ANALISIS KEBIJAKAN BANK INDONESIA TENTANG PENERAPAN MANAJEMEN RISIKO PADA BANK YANG MELAKUKAN PEMBERIAN KREDIT PEMILIKAN RUMAH (KPR) - ARBIATMA, FIQIHANI (Jurnal Akuntansi AKUNESA, 2013)
As the industry developed rapidly and has an increasingly diverse business activities, banksare faced with increasingly complex risks. One of the very rapid at this time is the provisionof credit to the implications of credit risk / substantial losses. In this study, focusing onBank Indonesia Policy Analysis About Application of Risk Management at Bank of ConductHome Ownership Loan (mortgage), which will do a picture search policy in managingcredit risk, find strengths and weaknesses of the policy, as well as identifying the barriersfaced and analyze the implications and effectiveness of the implementation of Credit RiskManagement.Key words: Risk Management, mortgages, LTV